It's our agenda now - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2002)
Agriculture made it back to the top of the global policy agenda at the World Summit on Sustainable Development (WSSD), in Johannesburg in August/September 2002, where it was part of the list of core topics: water, energy, health, agriculture and...